2020
DOI: 10.3389/fmed.2020.00312
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in Combination Treatment for Patients With Rheumatoid Arthritis

Abstract: Background: The aim of this study is to evaluate the clinical efficacy of vitamin D (VitD) supplementation in terms of response to treatment and improvement of disease activity in rheumatoid arthritis (RA). Methods: This study analyzed 1180 RA patients' records treated at Mianyang Central Hospital from February 2015 to July 2019. The patients were allocated into VitD group and control group based on their medical regimens. The outcome measures were primary efficacy, defined as treatment response-based EULAR re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Furthermore, in a small cohort of 61 patients with RA, supplementation with vitamin D (100,000 IU per month) resulted in a significant reduction in DAS28 in patients with sufficient basal serum concentrations of vitamin D and VAS in patients with deficient basal serum concentrations of vitamin D 125 . Conversely, some investigations have found no significant clinical benefit after vitamin D supplementation 126 130 .…”
Section: Vitamin D and Interconnections With Autoimmune Rheumatic Dis...mentioning
confidence: 99%
“…Furthermore, in a small cohort of 61 patients with RA, supplementation with vitamin D (100,000 IU per month) resulted in a significant reduction in DAS28 in patients with sufficient basal serum concentrations of vitamin D and VAS in patients with deficient basal serum concentrations of vitamin D 125 . Conversely, some investigations have found no significant clinical benefit after vitamin D supplementation 126 130 .…”
Section: Vitamin D and Interconnections With Autoimmune Rheumatic Dis...mentioning
confidence: 99%
“…A study showed that treatment with vitamin D supplementation in RA patients with secondary osteoporosis could effectively increase bone mineral density [29]. Nevertheless, a study involving 1180 individuals indicated that vitamin D supplementation did not provide other bene ts for anti-rheumatic therapy [30]. The speci c roles of vitamin D in the pathology of RA and whether vitamin D supplementation is effective remains to be con rmed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The most important point is the demonstrated different effects of cholecalciferol on DAS28 and VAS depending on baseline 25(OH)D levels: The most beneficial effects of cholecalciferol on DAS28 were found in patients with baseline 25(OH)D > 20 ng/mL, while its greatest effects on VAS were in patients with baseline 25(OH)D < 20 ng/mL [ 99 ]. However, in a recent study analyzing 1180 RA patient records, vitamin D supplementation did not provide additional benefit for anti-rheumatic treatment [ 100 ]. These data support the need for prospective, randomized, controlled trials (RCTs) to evaluate the role of vitamin D supplementation in treating RA.…”
Section: Vitamin D In Rheumatic Auto-immune Diseasesmentioning
confidence: 99%